Tu'a Golo's role in resolving land disputes between Poka indigenous people, Longko Village, Wae Ri'i District, Manggarai Regency - Marsianus Ampat; Yustinus Pedo; Ernesta Uba Wohon; Don Rade, Stefanus (Al Ahkam, 2023)
The Poka Indigenous People are part of the Manggarai community, also practicing matters related to Manggarai culture such as resolving land disputes between community members. This research was conducted to find out the role of Tu'a Golo in resolving disputes among the Indigenous People of the Poka Village, Longko Village, Wae Ri'i District, Manggarai Regency. Based on the results of the study, the role of Tu'a Golo in the Poka Indigenous People is to: Regulate and manage the socio-economic and cultural life of the community and resolve land boundary disputes of the Poka indigenous people. The role of Tu'a Golo in resolving land boundary disputes is as follows: 1) The role of Tu’a Golo in the dispute between Benyamin Bago and the Manggarai Regency Government. In this case, Tu'a Golo was presented by the police only as a witness. 2) The role of Tu’a Golo in the dispute between Alosius Sema and Benyamin Bago, namely: receiving and assessing community reports regarding the disputed dispute, leading the lonto leok event in resolving cases, summoning tu'a-tu'a panga and witnesses, leading the event of reviewing the location of cases, deciding cases, being a witness in a case. The decision of the old golo regarding the land boundary dispute between Alosius Sema and Benyamin Bago has binding force and applies to the parties, but is not final. According to the researcher, Tu’a Golo decision in the dispute between Alosius Sema and Benyamin Bago fulfilled the element of justice.